Algorithm Modeling in Islamic Geometric Pattern Reconfiguration: Case Study of Cheng Ho Mosque's Islamic Ornament - Fajar Ikhwan Harnomo; Andiyan Andiyan; Tita Cardiah; Tri Wahyu Handayani; Ayu Puspa Wirani; Rofiqul Umam; Nangkula Utaberta (Journal of Islamic Architecture, 2025)
The focus of this study is the issue of reorganizing the preexisting Islamic Geometric Patterns found at the Cheng Ho Mosque via the use of computer modeling techniques. The need for computer modeling research for rearranging geometric patterns at the Cheng Ho Mosque may be attributed to many factors. The objective is to use digitization to streamline the ornamental design process. The study methodology used included the analysis of geometric forms, which were then processed and patterned using Parametric Islamic Geometric Patterns with the assistance of Grasshopper software. This study employs the Islamic octagonal archetype, similar to Chinese geometric ornamentation, using circular geometry with a radius input, as discussed in the preceding article. The inclusion of the division shape serves as a necessary limitation to facilitate the cutting of the recurring patterns. The findings indicate that the algorithmic technique is constructed using a collection of parameter inputs organized into four primary components: octagonal basis geometry, repetition procedure, partition or boundary-shaped surface, and material dimension simulation. However, it also demonstrates varying parameter inputs, posing challenges in organizing them accurately to generate the octagonal form. Visual scripts may effectively depict Islamic geometry in open systems that exhibit parametric adaptability to the fundamental principles of division. During the design processing phase, it is possible to exert control over the pattern proportions in some instances.